EVALUASI PENGENDALIAN INTERNAL UTANG USAHA DI PT. TIGA PILAR LOGISTIK - DIAN PERMATA SARI, TABITA (JURNAL ILMIAH MAHASISWA AKUNTANSI, 2012)
Internal control is a protection for company from risks with ensuring data reliability and information, also increase affectivity in managed various company activity. Internal control is getting important in every company’s part, including in accounting. In evaluating company’s system, found various facts that weak internal control system could affect a couple problems with ineffective and inefficient work on expenditure system. The problems are: no reconcile between payable record and payable control account at general ledger that can causes registration different that affect in validity and data accuracy that presented in financial statement, with no proper authorization on company’s document. To mitigate the fraud, evaluation is needed in payable internal control. Evaluation towards existing expenditure system is needed to help company in handling problems about payable reconcile even important document authorization for company.